Robinson Crusoe on Mars [videorecording (DVD)] - Haskin, Byron, 1899-1984; Mantee, Paul; Lundin, Victor; West, Adam, 1928-2017; Defoe, Daniel, 1661?-1731 (Criterion collection, 2007)
When his spaceship crash-lands on the barren wastelands of Mars, U.S. astronaut Commander "Kit" Draper must fight for survival, with a pet monkey his only companion until he meets "Friday," an alien.